Meningkatkan Manajemen Bisnis dan Pengetahuan Literasi Keuangan dalam Kegiatan Micro Business Games - Yuttama, Faizal Rizky; Indrawati, Iin Dyah (Jurnal Pengabdian Masyarakat - PIMAS, 2024)
The micro, small and medium enterprises (MSME) sector is one of the components that drives indonesia’s economic growth. Bank Jateng supports the goverment’s efforts to advance MSMEs by holding Micro Business Games (MBG). MBG is very important for MSME actors and prospective players to increase their knowledge of business management and financial literacy. This community service activity acts as a sinergy to help understand business management and financial literacy as the efficiency and effectiveness of entrepreneurs.